Copyright Uploader Youtube Perspective of Positive Law and Islamic Law - Fachri Wahyudi; Muhammad Hanifannur (Journal of Southeast Asian Islam and Society, 2024)
In this era of advanced technology, humans can do everything online including the increasing number of applications that help humans create, innovate and work such as using the YouTube application. YouTube is included in the protected cinematographic copyright. A protected copyright work must have a distinctive and special form. In this era of technology and creative industries, there are many people who commit criminal acts of video piracy on the YouTube platform and even broadcast without permission and profit. But for the creator, it is very detrimental. The subject matter studied in this research is about how copyright protection for YouTube uploaders in Article 40 of Law Number 28 of 2014 concerning Copyright and the perspective of Islamic law on copyright protection for YouTube uploaders. This research is a normative legal research using legislative and normative Islamic approaches. The results showed that copyright protection of YouTube uploaders is regulated in Law Number 28 of 2014 concerning Copyright which is technically regulated in Article 40 paragraph (1) letter m, although not specifically mentioned in the article but there are similarities in audiovisual form. When viewed in Islamic law, the YouTube re-uploader's actions are included in the jarimah ta'zir whose punishment is given to Ulil Amri (the government). The protection of property rights is one of the objectives of Islamic law, including the dharuri needs of every human being. Therefore, when Islam recognizes copyright as one of the property rights of property, then the property rights will be protected as well as the protection of property.